Agricultural pesticide sprayers N1 - FAO (FAO, 1998)
The guidelines contain the following elements: *) Guides to the selection of agricultural pesticides sprayers and quality standards for spray equipment; **) Procedures for the worldwide introduction of equipment certification schemes for the FAO-approved status of new spray equipment; ***) Procedures for the organization of sustainable operator training and awareness programmes; ****) Recommendations for the organization of suitainable operator training and awareness programmes